(untitled) (TEST BioLaw Journal - Rivista di BioDiritto, 2021)
The article addresses, in necessarily succinct terms, the theme of the reconfiguration of the concept of "legal subjectivity" and of "legal personhood" as a fundamental legal status for the human being, due to the scientific and technological developments, both in the field of human biological life and of artificial intelligence, considering, in particular, the cases of embryos, organoids, and AI-systems.